Hyperbolic isocoronal tilings. Issue 2 (3rd July 2018) - Taganap, Eduard C.; De Las Peñas, Ma. Louise Antonette N.
ABSTRACT: This paper discusses a method that facilitates the systematic derivation of isocoronal tilings from isohedral tilings. The method is applied to construct isocoronal tilings in the hyperbolic plane and determine their symmetry groups. GRAPHICAL ABSTRACT: